Asymmetric Construction of an Aryl‐Alkene Axis by Palladium‐Catalyzed Suzuki–Miyaura Coupling Reaction. Issue 45 (6th October 2022) - Qiu, Sheng‐Qi; Chen, Yu; Peng, Xiang‐Jun; He, Shi‐Jiang; Cheng, Jun Kee; Wang, Yong‐Bin; Xiang, Shao‐Hua; Song, Jun; Yu, Peiyuan; Zhang, Junmin; Tan, Bin
Abstract: The application of Suzuki–Miyaura coupling reaction to forge the atropisomeric biaryls has seen remarkable progress but exploration of this chemistry to directly forge chiral C(aryl)‐C(alkene) axis is underdeveloped. The replacement of arene substrates by alkenes intensifies the challenges in terms of reactivity, configurational atropostability of product and selectivity control. By meticulous ligand design and fine‐tuning of reaction parameters, we identified a highly active 3, 3′‐triphenylsilyl‐substituted phosphite ligand to realize arene‐alkene Suzuki–Miyaura coupling of hindered aryl halides and vinyl boronates under very mild conditions. The axially chiral acyclic aryl‐alkenes were generated in commendable efficiency, enantioselectivity and E / Z selectivity. Abstract : The construction of axially chiral acyclic aryl‐alkene skeletons via classic Suzuki–Miyaura reaction has been challenging compared to the biaryls. Rational optimization established an enabling 3, 3′‐triphenylsilyl‐substituted phosphite ligand for asymmetric coupling of hindered aryl halides and vinyl boronates under mild conditions, affording the acyclic aryl‐alkenes in good yield, atroposelectivity and E / Z selectivity.